Experimental evolution of bacterial resistance to copper : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biological Science at Massey University, Auckland, New Zealand - Li, Xinyue (Massey University, 2020)
Hospital-acquired infections (HAIs) are a serious health concern worldwide. Currently in New Zealand, around one in ten patients admitted to hospitals will acquire an infection while receiving treatments for other diseases in hospitals. One of emerging strategies to reduce the risk of HAIs is to apply metallic copper on the commonly touched items, providing sustained protection against microbial contamination. This is owing to the fact that bacterial pathogens are rapidly killed on copper surfaces through a process termed contact killing. However, the mechanisms of contact killing still remains elusive. Research in our laboratory aims to elucidate the mechanism of copper-mediated contact killing and investigate the probable overlapping antimicrobial resistances to copper and antibiotics. Based on a previous experimental evolution, we found several different responses potentially conferring copper resistance: increased tolerance to copper ions, decreased pyoverdine production and elevated mutation rate. Also, consistent to our expectation, evolved copper-resistant strains showed altered levels of resistance to antibiotics such as tobramycin. Next, two unique approaches of experimental evolution were used to assess the potential of bacteria to develop resistance to ionic copper, involving colony-to-colony transfer and broth-to-broth transfer. Specifically, P. fluorescens SBW25 and P. aeruginosa MPAO1 were subjected to passage of sub-lethal concentrations of copper ions on LB agar and in LB broth. After several transfers, the evolved strains exhibited an increase of minimal inhibitory concentration of copper ions. Taken together, data presented in this thesis implicates potential evolutionary mechanisms of bacterial resistance to metallic copper, and further suggest the probable evolution of overlapping bacterial resistances to copper and antibiotics. Primary data were obtained for the experimental evolution of bacterial pathogen in the presence of toxic copper ions.
Figure 1.3 (=Mathews et al., 2013 Fig 2) was removed for copyright reasons. Figure 1.6 is reproduced under a Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/).
Keywords: 310701 Bacteriology